The biophysical processes controlling the South-East Madagascar Bloom - Dilmahamod Ahmad Fehmi (Department of Oceanography, 2019)
Phytoplankton blooms are ecological hotspots in the ocean, and are fundamental to the biogeochemical cycling of elements, the storage of carbon and the ability to regulate the atmospheric carbon dioxide; and the life in the ocean. The South-East Madagascar Bloom, one of the largest blooms in the global ocean, coexists with the poleward flowing South-East Madagascar Current (SEMC), the eastward flowing South Indian Ocean Countercurrent (SICC) as well as westward-propagating surface and subsurface-intensified eddies. This austral summer bloom extends largely towards the open ocean, from the Madagascan coasts up to ~65°E and it exhibits an intriguing interannual variability. A variety of observational datasets as well as a high resolution coupled physical-biogeochemical model, based on CROCOPISCES, are used to explore the biophysical processes associated with the bloom and these westward-propagating eddies. Based on historical observational data, the bloom is shown to occur in a region of shallow mixed layer, with the surface layer exhibiting lower salinity, a possible signature of the coastal poleward flowing SEMC waters. The testing of various hypotheses revealed a dampening of the coastal current-driven upwelling south-east of Madagascar during bloom months. A dipole mesoscale feature is also prevalent close to the Madagascan coast during the bloom, from which a new hypothesis emerges. This new hypothesis states that the region south/south-east of Madagascar, influenced by local mesoscale turbulence, acts as a gate for the SEMC to flow either towards the African continent, or into the bloom region through an early retroflection, hence fertilizing the bloom. The model produces a sporadic enhancement of chlorophyll-a in the subsurface levels, associated with a low-salinity surface signature. The mean local circulation associated with the simulated bloom also reveals a dipole structure, as in observed datasets. Nitrate from subsurface levels (upwelling) as well as from the Madagascan coast (advection) is shown to influence the simulated bloom. A Lagrangian experiment shows dispersion of higher percentages of particles in the bloom region during bloom years and south of Madagascar during non-bloom years. Mesoscale eddies, originating close to Australia and which propagate westward towards southern Africa, can potentially impact the South-East Madagascar Bloom. In this study, a vast majority of these features have been shown to be subsurface-intensified eddies. A co-located eddy tracking dataset with Argo profiling floats are used to devise a subsurface-eddy identification method, which is based on the steric dynamic height anomaly of a specific eddy. Adding to the `eddy-zoo', these eddies are termed `SIDDIES' (South Indian ocean eDDIES), occurring as surface (surfSIDDIES) and subsurface (subSIDDIES) features. They travel along the latitudinal band range of 15°S to 35°S which we name the ‘SIDDIES corridor’. Advecting warm and fresh water during their propagation, cyclonic (anticyclonic) subSIDDIES contribute about 58% (32%) of the total eddy-heat flux in the South Indian Ocean. Anticyclonic subSIDDIES have also been found to be the sole, high-saline water eddy-conveyor towards the western South Indian Ocean. These eddies could also possibly transport nutrients throughout their journey, impacting the biogeochemistry of the ocean near Madagascar.